2021
DOI: 10.3390/toxics9080196
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Risk Assessment of Amoxicillin, Enrofloxacin, and Neomycin: Are Their Current Levels in the Freshwater Environment Safe?

Abstract: Veterinary pharmaceuticals may cause unexpected adverse effects on non-target aquatic species. While these pharmaceuticals were previously identified as priority compounds in ambient water, their ecological risks are relatively unknown. In this study, a series of chronic toxicity tests were conducted for these pharmaceuticals using algae, two cladocerans, and a fish. After a 21-d exposure to amoxicillin, enrofloxacin, and neomycin, no observed effect concentration (NOEC) for the reproduction of Daphnia magna w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 61 publications
0
10
0
1
Order By: Relevance
“…Pharmaceuticals in the environment are a recurring problem that threatens human health and ecosystem balance due to their widespread availability. Pharmaceuticals are designed for specific therapeutic functions and may cause unexpected physiological effects on non-target species [ 1 ]. The potential consequences of these compounds in the environment have to be considered seriously, and growing attention has been directed to pharmaceuticals in ecological systems.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Pharmaceuticals in the environment are a recurring problem that threatens human health and ecosystem balance due to their widespread availability. Pharmaceuticals are designed for specific therapeutic functions and may cause unexpected physiological effects on non-target species [ 1 ]. The potential consequences of these compounds in the environment have to be considered seriously, and growing attention has been directed to pharmaceuticals in ecological systems.…”
Section: Introductionmentioning
confidence: 99%
“…Given that only about 25% of antibiotics are effectively used in aquaculture, the animal body poorly absorbs most antibiotics, and 30–90% of antibiotics are excreted via urine and feces into the environment. Consequently, antibiotics are frequently detected in surface water, groundwater, soils, and sediments [ 1 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the surface waters of these countries with concentrations ranging from less than 1 ng L -1 to hundreds of µg L -1 . Lee et al (2021) evaluated the environmental risks of the antibiotics Amoxicillin, Enrofloxacin, Neomycin on the aquatic environment, where the study conducted a series of toxicity tests for these antibiotics on algae and bacteria, The results indicated that Amoxicillin and Enrofloxacin are antibacterial that cause great concerns for the environment, and that more efforts, studies and investigations are needed to investigate the environmental consequences caused by both antibiotics. As for the antibiotic Neomycin, where the study confirmed that the environment in the surrounding waters must be monitored before it can properly describe its environmental risks.…”
Section: Introductionmentioning
confidence: 99%